Development of a Biology Magazine as Learning Material for the Human Regulatory System: Validity and Student Attractiveness Evaluation - Noverlia Astrid Kartika; Nevi Amalia (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to develop a magazine-shaped biology learning media on the regulatory system material and to determine the level of feasibility and attractiveness of the product based on expert validation results and student responses so that it can be used as teaching material in biology learning. Methodology: This study employed the Research and Development (R&D) method with the Sugiyono development model, extending to the product revision stage. Data collection was conducted using a validation questionnaire and student response questionnaire. The instrument was validated by subject matter experts, media experts, and language experts. Data analysis used descriptive statistics in the form of percentages on a five-level Likert scale to determine the product's feasibility and attractiveness. Main Findings: The results of the study showed that the magazine-based learning media received a feasibility rating of 83% from material experts, 90% from media experts, and 93% from language experts, all of which were categorized as very feasible. Student responses in the trial averaged 88%, categorized as very interesting, thus the media was declared suitable for use as teaching material for the regulatory system topic. Novelty/Originality of this study: This research has produced a biology learning medium in the form of a magazine that integrates the presentation of regulatory system material with colorful illustrations, communicative language, and contextual information in one engaging printed material. The developed product not only meets the feasibility criteria but also enhances student learning engagement, making it an innovative alternative in biology instruction.